On certain classes of p-Valent functions by using complex-order and differential subordination. - Kilicman, Adem; Tehranchi, Abdolreza (Hindawi Publishing Corporation, 2010)
The aim of the present paper is to study the p-valent analytic functions in the unit disk and satisfy the differential subordinations z(Ip)r, ?(f(z))(j+1)/(p - j)(?p(r, ?)f(z))(j) < (a + (aB + (A- B)ß)z)/a(1 + Bz), where ?p(r, ?) is an operator defined by Salagean and ßis a complex number. Further we define a new related integral operator and also study the Fekete-Szego problem by proving some interesting properties.